Development of computer aided tool for torsional vibration analysis of marine propulsion system [electronic resource] - Faizul Ali Adam, 1990-, author 635171; Nasrudin Ismail, supervisor 195632; Fakulti Kejuruteraan Mekanikal 8081 (2014)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2014